Risk and Response Adapted Treatment Guidelines for Managing First Relapsed and Refractory Classical Hodgkin Lymphoma in Children and Young People. Recommendations from the EuroNet Pediatric Hodgkin Lymphoma Group - Daw, Stephen; Hasenclever, Dirk; Mascarin, Maurizio; Fernández-Teijeiro, Ana; Balwierz, Walentyna; Beishuizen, Auke; Burnelli, Roberta; Cepelova, Michaela; Claviez, Alexander; Dieckmann, Karin; Landman-Parker, Judith; Kluge, Regine; et al. (HemaSphere, 2020)
The objective of this guideline is to aid clinicians in making individual salvage treatment plans for pediatric and adolescent patients with first relapse or refractory (R/R) classical Hodgkin lymphoma (cHL). While salvage with standard dose chemotherapy followed by high dose chemotherapy and autologous stem cell transplant is often considered the standard of care in adult practice, pediatric practice adopts a more individualized risk stratified and response adapted approach to salvage treatment with greater use of non-transplant salvage. Here, we present on behalf of the EuroNet Pediatric Hodgkin Lymphoma group, evidence and consensus-based guidelines for standardized diagnostic, prognostic and response procedures to allocate children and adolescents with R/R cHL to stratified salvage treatments.